2006
DOI: 10.1021/ma052248k
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystals of Chain-Folded Copolyterephthalamides

Abstract: sciences et inge ´nierie des macromole ´cules, Faculte ´des sciences et de ge ´nie, UniVersite ´LaVal, Que ´bec, Que ´bec, Canada G1K 7P4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…These vary, on average, from 37 to 50%, but contrarily to the PPTA-based copolymers (13), no significant effect of chain length was found in this case. Crystallinity were also investigated using X-ray diffraction, with has two main assets: no thermal degradation, and the possibility of ascertaining which of the crystal forms was obtained.…”
Section: Characterization Of the Rigid-flexible Copolymersmentioning
confidence: 54%
See 1 more Smart Citation
“…These vary, on average, from 37 to 50%, but contrarily to the PPTA-based copolymers (13), no significant effect of chain length was found in this case. Crystallinity were also investigated using X-ray diffraction, with has two main assets: no thermal degradation, and the possibility of ascertaining which of the crystal forms was obtained.…”
Section: Characterization Of the Rigid-flexible Copolymersmentioning
confidence: 54%
“…The present work will focus on a variation of the rigid blocks size, the spacer in this case being a simple short alkyl chain. Our group has previously shown that incorporation of rigid, crystalline oligo(para-phenyleneterephthalamide) rigid blocks alternating with short flexible spacers led to copolymers which form a single phase and which retain a high crystallinity (12,13). It was also found that rigid block polydispersity resulted in a marked crystallinity decrease.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR (cm -1 ): 2922 (δ a aliphatic (C-H)), 2851 (δ s aliphatic (C-H)), 1656 + 1640 (amide I), 1553 (amide II). 1 …”
Section: Synthesis Of 3ara-c10mentioning
confidence: 99%
“…FTIR attenuated total reflectance spectra (ATR) spectra of molecules and of mpI were also taken, using a resolution of 4 cm -1 , using the same spectrometer, using a Golden Gate sample holder and a DTGS detector in the 4000-530 cm -1 spectral domain. 1 H NMR spectra were recorded on a Bruker AC-300 apparatus functioning at 300 MHz, using tetramethylsilane (TMS) as an internal reference. The spectra consisted of 16 acquisitions and were analyzed using the SpinWorks version 1.3B software.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation